A Bullet Entered through the Open Mouth and Ended Up in the Parapharyngeal Space and Skull Base. (7th June 2015) - Goswami, Saileswar; Goswami, Choitali
Abstract : Shot from a revolver from a close range, a bullet pierced the chest of a policeman and entered through the open mouth of a young male person standing behind. The entry wound was found in the cheek mucosa adjacent to the left lower third molar. After hitting and fracturing the body and the ramus of the mandible, the bullet was deflected and was finally lodged in the parapharyngeal space and skull base, anterolateral to the transverse process of the atlas. The great vessels of the neck were not injured. The patient's condition was very critical but his life could be saved. The bullet was approached through a modified Blair's incision and was found to be lying over the carotid sheath. It was removed safely and the patient recovered completely.